The efficacy and safety of acupuncture for Parkinson’s disease insomnia: a systematic review and meta-analysis - Gu, Yujie; Liang, Yue; Han, Hui; Yin, Huichao; Zheng, Zuncheng (Frontiers in Neurology, 2025)
BackgroundInsomnia is a common comorbid symptom in Parkinson’s disease (PD) patients, significantly impairing their quality of life. Acupuncture is widely applied in treating PD insomnia, yet relevant evidence remains fragmented.ObjectiveTo investigate the efficacy of acupuncture in improving PD insomnia through systematic review and meta-analysis, evaluating its clinical effectiveness and safety.MethodsEight electronic databases were searched: PubMed, Cochrane Library, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), VIP Data Platform, Wanfang Data Knowledge Service Platform, and China Biomedical Literature Service System. References from relevant literature and clinical trial registries were manually searched for randomized controlled trials (RCTs) on acupuncture for PD insomnia. Studies were screened against inclusion and exclusion criteria, relevant data extracted, and meta-analysis conducted using RevMan 5.4 software.ResultsEleven studies involving 800 patients were included. Meta-analysis revealed that acupuncture effectively improved PSQI (MD = −2.87, 95% CI: −4.28 to −1.46, p < 0.0001) and PDSS (MD = 7.96, 95% CI: 5.55–10.37, p < 0.00001), demonstrating superior efficacy compared to the control group (MD = 6.64, 95% CI: 3.47–12.69, p < 0.00001).ConclusionAcupuncture effectively improves PSQI and PDSS scores in patients with PD insomnia and exhibits superior efficacy over the control group. However, due to limitations, further details could not be explored.